Answers

2016-04-12T08:39:40+05:30
(–15) × [(–7) – (–1)]

= (-15) 
× [-7+1]
= (-15) × (-6)
= 90

(–15) × (–7) – (–15) × (–1)

= 105 - 15
=90

Yes (–15) × [(–7) – (–1)]  =  (–15) × (–7) – (–15) × (–1)
0
2016-04-14T16:52:05+05:30
In L.H.S= (-15) x [(–7) – (–1)] 
             = -15 x ( -7+1)
             = -15 x (-6)
             = 90
in R.H.S= (-15) x (-7)-(-15) x(-1)
             = 105 + 15 x(-1)
             =105 + (-15)
             = 105-15 = 90
 as L.H.S= R.H.S
(–15) × [(–7) – (–1)] = (–15) × (–7) – (–15) × (–1)
1 5 1